2020
DOI: 10.1111/biom.13337
|View full text |Cite
|
Sign up to set email alerts
|

Resampling‐based confidence intervals for model‐free robust inference on optimal treatment regimes

Abstract: We propose a new procedure for inference on optimal treatment regimes in the model‐free setting, which does not require to specify an outcome regression model. Existing model‐free estimators for optimal treatment regimes are usually not suitable for the purpose of inference, because they either have nonstandard asymptotic distributions or do not necessarily guarantee consistent estimation of the parameter indexing the Bayes rule due to the use of surrogate loss. We first study a smoothed robust estimator that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…In order to handle these two challenges, we consider the smoothing methods. [35][36][37] Let (⋅) be a differentiable bounded continuous function satisfying  s→−∞ (s) = 0,  s→+∞ (s) = 1 and some regularity conditions. 35 We use the kernel smooth function  (…”
Section: Penalized Smoothed Inverse Probability Weighted Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to handle these two challenges, we consider the smoothing methods. [35][36][37] Let (⋅) be a differentiable bounded continuous function satisfying  s→−∞ (s) = 0,  s→+∞ (s) = 1 and some regularity conditions. 35 We use the kernel smooth function  (…”
Section: Penalized Smoothed Inverse Probability Weighted Estimationmentioning
confidence: 99%
“…Second, existing work on threshold regression showed that the asymptotic distribution of the direct estimators for threshold coefficients are often nonstandard, 16,17,19 which is too complicated for statistical inference. In order to handle these two challenges, we consider the smoothing methods 35‐37 . Let 𝒦false(·false) be a differentiable bounded continuous function satisfying 𝒦s(s)=0, 𝒦s+(s)=1 and some regularity conditions 35 .…”
Section: Models and Estimatesmentioning
confidence: 99%
“…Motivated by Wu and Wang (2021) for mean-optimal treatment regime with complete data, we consider the following smoothed estimator…”
Section: Smoothed Resampling Inferencementioning
confidence: 99%
“…Replacing the indicator function in the treatment regime by the kernel function helps alleviates the sharp edge effect. Write Wu and Wang (2021), it is expected that √ nh β − β 0 is asymptotically normal. Note that β n minimizes the loss function…”
Section: Smoothed Resampling Inferencementioning
confidence: 99%
“…OPE is an important problem in settings where it is expensive or unethical to directly run an experiment that implements the target policy. This includes applications in precision medicine (Murphy;2003;Chakraborty and Murphy;2014;Matsouaka et al;2014;Gottesman et al;Wu and Wang;2020), autonomous driving 2020),robotics (Kober et al;, natural language processing , education (Mandel et al;2014), among many others. This paper is concerned with OPE under infinite horizon settings where the number of decision points is not necessarily fixed and is allowed to diverge to infinity.…”
Section: Introductionmentioning
confidence: 99%